Optimizing the Supervisory Role of the Consumer Dispute Settlement Agency in E-Commerce Transactions Concerning Consumer Losses - Haezer Josuo Tio Marpaung; Aurora Jillena Meliala (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
The rapid development of digital technology has shifted the conventional trading paradigm into e-commerce transactions, which, despite offering efficiency, are highly prone to causing complex disputes between consumers and business actors. To address these potential losses, Law Number 8 of 1999 concerning Consumer Protection mandates the establishment of the Consumer Dispute Settlement Body (BPSK) as an institution tasked with supervision and dispute resolution outside the court to ensure legal certainty. This research employs a juridical-empirical method with statutory and conceptual approaches to analyze the optimization of BPSK's supervisory role and its obligations in handling consumer losses. Research data were collected through in-depth literature studies and exclusive interviews with BPSK officials to comprehensively examine the implementation of the institution's policies, functions, and authorities within the current practice of consumer protection. The results indicate that optimizing BPSK's role as a supervisor faces significant structural obstacles due to the centralization of authority to the provincial level following the enactment of the Local Government Law, as well as the absence of technical guidelines for standard clause supervision, which causes overlapping functions with trade agencies. In the specific context of e-commerce, BPSK's supervision tends to be reactive on the downstream side, acting only after complaints are lodged, while upstream electronic system supervision remains under the control of the Ministry of Trade; a condition exacerbated by the fragmentation of complaint data which has not been integrated across institutions. Regarding the restoration of rights, BPSK has proven effective in adjudicating measurable material damages, such as refunds or product replacements, through conciliation, mediation, or arbitration dispute resolution mechanisms. However, BPSK has significant limitations in handling immaterial losses due to the difficulty of measuring psychological damage parameters and the weak executorial power of its decisions, which often fail if challenged in district court, making the effectiveness of consumer protection currently highly dependent on active consumer participation and voluntary business compliance.